Hybrid Teamwork: What We Know and Where We Can Go From Here - Handke, Lisa; Aldana, Aliza; Costa, Patrícia L.; O’Neill, Thomas A. (Small Group Research, 2024)
Hybrid teamwork, which describes any combination of one’s work time spent across organizational and other (typically domestic) work settings, has become a critical aspect of modern work environments. However, despite the rising prevalence and technological support for hybrid teamwork, there is limited understanding of its impact at the team level. Although we still lack research that addresses the dynamic geographic configurations inherent to hybrid teamwork, we believe that much of the extant literature on virtual teamwork can inform our understanding and guide future research. Accordingly, this paper aims to advance knowledge on hybrid teamwork by defining its unique characteristics and critically reviewing three broad classes of theory from the virtual teams literature and their implications for understanding hybrid teamwork. Based on both contributions and limitations of these three theory classes, we conclude this paper by mapping out pressing questions to guide future research.
CRIS-Team Scopus Importer:2024-09-20
Keywords: hybrid work; technology use; virtual teams